Influence of Railway on the Development of the Port of Ploce - Stipetić, Antun; Bagić, Željko; Starčević, Martin (Promet - Traffic&Transportation, 2006)
The role of the railway in the development of every cargoport is huge, since the railway enables mass transport of goods.Therefore the influence of the railway on the development ofthe Port of Place is significant, especially in the context of connectingthe port with the Pan-European Corridor Vc. The paperstudies the possibilities of improving the transport of goodsfrom the Port of Ploce by rail and the influence of this type ofcarriage on the development of the p01t.